THE MODERATING ROLE OF MARKET STRUCTURE ON THE RELATIONSHIP BETWEEN FIRM OPERATIONAL PERFORMANCE AND DEGREE OF OPERATING LEVERAGE - Lourenço, Wesley Da Silva; Louzada, Luiz Cláudio; Novaes, Paulo Victor Gomes (Revista Universo Contábil, 2019)
This article investigates the moderation role of market structure on the relationship between operational performance and firms’ costs composition. The Herfindahl-Hirschman Index (HHI) were adopted as proxy for market structure; for operational performance, Return on Invested Capital (ROIC); and for firms’ cost choices, the Degree of Operating Leverage (DOL). The database covers non-financial firms at Brazilian market from 1996 to 2016, third quarter. The output points toward to market structure moderation of the relationship between ROIC and DOL with an increase of the effect when markets move to a monopolistic structure. Overall results suggest the existence of a relation between firms’ operational performance and cost behavior, indicated by a negative relationship between ROIC and DOL. Furthermore, we notice a moderating role of Size on market structure (HHI) moderation role on the relationship between ROIC and DOL, in the extent that market structure moves towards a higher concentration level configuration, the moderating effect of HHI becomes more latent.